AT1 receptors in striatum DA-uptake: Crucial role and relevance in an Amphetamine-sensitization model of Schizophrenia - Basmadjian, Osvaldo Martin (2019)
Limbic dopamine (DA) hyperactivity, a hallmark of amphetamine (AMPH) exposure, it is considered as a neurochemical feature involved in the expression of schizophrenic positive symptoms. DA neurotransmission dynamics is regulated by the uptake of extracellular transmitter at presynaptic neurons through specific transporter. Angiotensin II, through AT1 receptors (AT1-R), modulates DA neurotransmission at limbic areas. Herein, we studied AT1-R involvement after AMPH exposure on: a) development and expression of behavioral sensitization, b) in vitro striatum DA uptake. To these purposes male Wistar rats (250-300 g) were daily administered with d-AMPH (2.5 mg/kg i.p.) for 5 days. After 3 weeks of withdrawal, the behavioral sensitization was evaluated measuring locomotor activity. The AT1-R blocker, Candesartan (CV 3 mg/kg p.o.), was administered daily for 10 days, starting 5 days prior to the first AMPH injection in the prevention sensitization protocol. In the reversion protocol, either, CV or aripiprazole (antipsychotic drug widely use partial agonist of D2 receptors), were administered for 5 days starting 2 weeks after the last AMPH injection. DA uptake was measured in homogenized striatum using an electrochemical sensor, based on glassy carbon electrode modified with carbon nanotubes and polyethylenimine by amperometry. The results were analyzed by 2-way ANOVA followed by Bonferroni test or t-test. We found that behavioral sensitization was prevented and reversed by AT1-R blockade more efficiently than aripiprazole. Moreover, 5 days of CV administration increased DA uptake fact that could account for the behavioral results. We conclude that the lesser DA signaling, as a result of the increasing of its uptake, would explain the beneficial effects of AT1-R blockade in the behavioral neuroadaptations induced by AMPH.